Microhabitat partitioning of closely related Sarawak (Malaysian Borneo) frog species previously assigned to the genus Hylarana (Amphibia: Anura) - Ramlah, Zainudin; Badrul Munir, Md Zain; Norhayati, Ahmad; Shukor, Mohd Nor (Tubitak Publisher, 2017)
Microhabitats play an important role as resources that are partitioned between phylogenetically related or ecologically similar species (i.e., a guild). This hypothesis was tested by first elucidating phylogenetically closed Sarawak frog species via DNA sequencing of the 16S rRNA mitochondrial DNA gene, and later determining their microhabitat guild and partitioning via nonmetric dimensional scale. Mitochondrial 16S gene revealed 5 monophyletic groups consisting of Hylarana erythraea + Amnirana icobariensis, Chalcorana raniceps, Abavorana luctuosa, Pulchrana signata + P. picturata, and P. baramica + P. glandulosa + P. laterimaculata. On the other hand, microhabitat utilization grouped the frogs into 5 ecological guilds consisting of semiarboreal species at the forest edge (C. raniceps), ground dwellers in an unforested region (H. erythraea), ground dwellers (rock) at the forest edge (P. picturata), ground dwellers on the forest floor and forest edge species (P. signata, P. glandulosa, A. luctuosa, O. hosii), and semiarboreal forest (riverine) species (P. baramica). Thus, the microhabitats used were not influenced by the proposed phylogenetic relationships. Partitioning of microhabitat utilization, on the other hand, was clearly seen in 2 closely related species in both vertical and substrate utilization. The study supports resource partitioning by closely related species reflected by their ecological guilds, and will be useful for conservation management of the Bornean fauna.